Case Report: A personalized model of care for surgical resection of complex brain tumor with atypical language dominance - Sherry, Natalie; Gecici, Neslihan Nisa; Stepniak, Amelia; Miller, Daniel; Habib, Ahmed; Niranjan, Ajay; Barrios-Martinez, Jessica; Yeh, Fang-Cheng; Balzer, Jeffrey; Zinn, Pascal O. (Frontiers in Neuroscience, 2025)
The gold standard for preserving language and cognitive function during complex brain tumor resection is direct electrical stimulation (DES) during awake craniotomy. DES is predominantly utilized for left hemisphere (LH) tumors, where language dominance is most common. However, atypical language dominance and functional reorganization due to tumor growth are increasingly recognized and can complicate preoperative planning. We present the novel case of a 58-year-old monolingual, English-speaking, strongly right-handed male with recurrent right temporal glioblastoma who exhibited right hemisphere (RH) language dominance based on multimodal preoperative evaluation. The patient had no known perinatal or neurodevelopmental history, and he had previously undergone tumor resection under general anesthesia, with no postoperative aphasia. An awake craniotomy with intraoperative mapping (IOM) was performed, which confirmed language representation in the right frontal and temporal lobes. This was further substantiated by neuropsychological testing (NPT), which revealed a decline in semantic language postoperatively. This case challenges the prevailing practice of limiting awake procedures to LH tumors and supports a personalized, multimodal approach to mapping eloquent cortex irrespective of tumor laterality to optimize surgical outcomes.